2006
DOI: 10.1016/j.geoderma.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium stabilization controls organic carbon levels in Chilean volcanic soils

Abstract: Chilean volcanic soils are known to contain large amounts of organic matter (OM) and amorphous (e.g., allophanic) clay. Here, we test the hypothesis that Al, rather than clay content and climatic conditions, is the most important factor for OM levels in volcanic soils. This was achieved by compiling a total of 225 pedons from two national-wide datasets of south-Central Chilean soils sampled in the first 20 cm depth. All selected soils are of volcanic origin, previously under native Nothofagusforest and now use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 15 publications
6
43
0
4
Order By: Relevance
“…However, in kaolinitic soils, more crystallinity clay exerted a small stabilizing effect. In previous studies, Al-SOM complexes was the primary factor explaining soil C variation in similar soils rather than climatic variables and clay content (Percival et al, 2000;Matus et al, 2006). Neculman et al (2012) found an inverse relationship between soil pH and C pyrophosphate, supporting the hypothesis that the Al-SOM complexes and allophane formation are inverse, although complementary processes are mainly regulated by soil pH (Garrido and Matus, 2012;Panichini et al, 2012).…”
Section: Relationship Between Metabolic Quotient (Qco 2 ) and C Stabimentioning
confidence: 54%
See 2 more Smart Citations
“…However, in kaolinitic soils, more crystallinity clay exerted a small stabilizing effect. In previous studies, Al-SOM complexes was the primary factor explaining soil C variation in similar soils rather than climatic variables and clay content (Percival et al, 2000;Matus et al, 2006). Neculman et al (2012) found an inverse relationship between soil pH and C pyrophosphate, supporting the hypothesis that the Al-SOM complexes and allophane formation are inverse, although complementary processes are mainly regulated by soil pH (Garrido and Matus, 2012;Panichini et al, 2012).…”
Section: Relationship Between Metabolic Quotient (Qco 2 ) and C Stabimentioning
confidence: 54%
“…Regression analysis to test the effect of soil properties on C mineralization were conducted following the approach used by Matus et al (2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can occur whenever organic compounds become adsorbed to mineral surfaces (Kaiser and Guggenberger 2000;Kalbitz et al 2005), but also when the concentration of cations becomes sufficient for soluble organic polymers to flocculate and precipitate (Baldock and Skjemstad 2000). Much of the research on flocculation thresholds has focused on acid soils dominated by Al chemistry (Boudot 1992;Matus et al 2006;Rasmussen et al 2006). In these soils, it has been shown that extensive flocculation and precipitation can be expected at a C:Al ratio in the order of 10-30 or lower (Jansen et al 2003;Scheel et al 2007;Skjemstad et al 1992).…”
Section: Bonding Mechanismsmentioning
confidence: 99%
“…Aggregates containing clays and Al and Fe oxides or hydroxides promote soil organic C incorporation conferring aggregate stability, especially in volcanic soils. Recently, Matus et al (2006) have demonstrated that soil organic matter accumulation in Chilean volcanic soils is produced by Al stabilization rather than climatic conditions and clay content of soils. Bivalent cations such as Ca and Mg also improve soil aggregation in the same way as trivalent cations above mentioned.…”
Section: Soil Properties Contributing To Soils Aggregationmentioning
confidence: 99%